Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Dinas Pendidikan Kabupaten Bogor - Andri Mulya Sopian; Muhamad Azis Firdaus; Anuraga Kusumah (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to test and analyze the effect of motivation and work discipline on the performance of employees of the Bogor Regency Education Office. Data collection was carried out by distributing questionnaires with a sample size of 50 respondents and using a quantitative descriptive approach. Therefore, the data analysis used is statistical analysis in the form of simple and multiple linear regression tests. The results of this study indicate that partially and simultaneously the variables of motivation and discipline affect the performance of employees of the Bogor Regency Education Office. This is evidenced by the results of the Partial Test (t test) and simultaneous test (F test) which also shows the significant value of the two independent variables that support the hypothesis. Therefore, the test results of this study state that there is a simultaneous influence between the variables of motivation and discipline on the performance of the Bogor Regency Education Office.